교육용 콘텐츠 사업 및 성과관리 체계 개발 -CIPP를 중심으로 - 나지영(Young Na) (디지털콘텐츠학회논문지, 2022)
교육부는 양질의 콘텐츠를 통해 교육 현장의 효율성을 높이고자 2018년부터 약 200억의 예산을 투입하였으나, 콘텐츠 관리 기준이 없어 개선이 필요한 시점이다. 이에 본 연구는 교육용 콘텐츠 사업 및 성과관리 체계를 구축하여 체계적인 콘텐츠 관리 기준을 마련하고 한다. CIPP 평가 모형을 중심으로 성과관리 프레임워크를 개발하였으며, AHP 분석을 통해 가중치를 부여하여 평가 지표를 완성하고, 정의서를 개발했다. AHP 연구 결과 주요인에서는 ‘성과 및 환류 단계’, 세부 요인에서는 ‘개발 단계별 예산계획은 적절했는가?’ 요인이 가장 중요한 것으로 나타났다. 개발한 평가 지표는 상황, 투입, 과정, 산출 등 4개 평가 영역에 17개의 성과관리 평가 지표를 포함한다. 이를 통해 교육 콘텐츠 관련 사업 및 성과 관리를 강화하여 교육 현장에 양질의 콘텐츠를 보급하는 데 기여하고자 한다. Despite the Ministry of Education’s investment of about 20 billion won since 2018 for increase in efficiency of the educational field, improvement in the performance is demanded as there is no content management standards. Accordingly, this study is intended to establish systematic content management standards by constructing an educational content business and performance management system. Performance management framework was developed with CIPP evaluation model as the center, and evaluation index was completed by weighting through AHP analysis and the definition was developed. According to the AHP findings, the most important factors were “Outcome and reflux stage” in the case of the main factors and “Was the budget plan by development stage appropriate?” in the case of the detailed factors. The developed evaluation indicators include 17 performance management evaluation indicators in four evaluation areas: situation, input, process, and output. Based on this, hopefully it will contribute to the distribution of high-quality content to the educational field by strengthening educational content-related businesses and performance management. KCI Citation Count: 1